Skinny habits ebook The 6 secrets of thin people. - Harper, Bob (Skinny Rules., 2015)
Bob Harper lets us in on the secret behaviors of people who not only lose weight but keep the pounds off for good—and make it look easy.   In Bob Harper’s #1 New York Times bestselling book The Skinny Rules, the trusted trainer and coach of NBC’s The Biggest Loser laid out the twenty nonnegotiable eating rules for getting thin.   In the process of helping countless men and women reach their weight loss goals, Harper has noticed six fundamental patterns in the lifestyle choices of those who succeed long-term—from the unique way they plan ahead to how they organize their environment and social calendars to even the way they dress. With his signature authority, colorful stories, and real-world solutions, Harper draws on the most up-to-date research related to habit formation, neuroplasticity, and cognitive behavioral psychology to show how feeding your brain—“the muscle between your ears”—can wield as much control over your weight as what you put in your mouth.   With anecdotes about his clients, guided steps for adopting your new practices, and tips for integrating them into your own daily routine, Skinny Habits has everything you need to shape your body and your life!